Short maternal stature and gestational weight gain among refugee and migrant women birthing appropriate for gestational age term newborns: a retrospective cohort on the Myanmar-Thailand border, 2004–2016 - Rose McGready; Ahmar H Hashmi; Verena I Carrara; Sue J Lee; Aung Myat Min; Mary Ellen Gilder; Nay Win Tun; Lay Lay Wah; Mu Wah; Elsi Win; Ma Ner; Prakaykaew Charunwatthana; et al. (BMJ Global Health)
Introduction To examine the interactions between short maternal stature, body mass index (BMI) and gestational weight gain (GWG) among appropriate for gestational age (AGA) term newborns in a population of refugees and migrants in Southeast Asia.Methods This is a retrospective cohort study from 2004 to 2016, including women delivering term, singleton newborns, with first trimester height, weight and gestation dated by ultrasound and a last body weight measured within 4 weeks of birth. AGA newborns were those not classified as small for gestational age or large for gestational age by either INTERGROWTH-21st or Gestation Related Optimal Weight standards. The influence of maternal stature on GWG in delivering an AGA newborn was analysed, with GWG compared with existing National Academy of Medicine (NAM) recommendations.Results 4340 women delivered AGA newborns. Mean maternal height (SD) was 151.5 cm (5.13), with 58.5% of women considered too short by INTERGROWTH-21st standards. Only one in four women (26.5%, 1150/4340) had GWG within NAM recommendations. Women of shorter stature had a significantly lower mean GWG compared with taller women in underweight and normal BMI categories (p<0.001 for both BMI categories). Mean GWG of overweight and obese women did not differ by height (p=1.0 and p=0.85, respectively) and fell within the lower range of NAM recommendations.Conclusion These results suggest that short maternal stature can be an important predictor of GWG and should be considered with prepregnancy BMI. Limited-resource settings and special populations need robust GWG recommendations that reflect height and BMI.